Implementasi Nilai Demokrasi Pada Organisasi Siswa Intra Sekolah Di SMK Negeri 1 Bulango Utara Kabupaten Bone Bolango - Harun, Hasnita; Ngiu, Zulaecha; Wantu, Asmun W. (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine whether democratic values ​​have been implemented in the Intra-School Student Organization of SMK Negeri 1 Bulango Utara. The subjects in this study were OSIS members. The method used in this study is a qualitative method. It aims to find data on whether democratic values ​​have been implemented or not in the Intra-School Student Organization. This study is divided into 2 research focuses, including 1) how is the implementation of democratic values ​​in the intra-school student organization at SMK Negeri 1 Bulango Utra. 2) what are the supporting and inhibiting factors for the implementation of democratic values ​​in the Intra-School Student Organization. Based on the results of this study, it can be concluded that democratic values ​​have been implemented well in the Intra-School Student Organization of SMK Negeri 1 Bulango Utara through OSIS activities, namely 1) OSIS Management Meeting. 2) Election of the OSIS chairman. 3) OSIS Grand Deliberation. The democratic values ​​formed in OSIS are, 1) Tolerance. 2) Freedom of expression. 3) Openness in communication 4) Mutual respect. 5) Togetherness. Supporting factors for the implementation of democratic values ​​in the intra-school Student Organization at SMK Negeri 1 Bulango Utara are 1) The school. 2) Student motivation. 3) The will of the students. Inhibiting factors for the implementation of democratic values ​​in the intra-school Student Organization at SMK Negeri 1 Bulango Utara are 1) apathetic students. 2) Limited student participation. 3) Low student motivation.